EFFECT OF FIRM SIZE AND DEBT TO ASSET RATIO ON EARNING PER SHARE WITH PROFITABILITY AS A MODERATING VARIABLES IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE IDX - pohan, Syahrial hasanudin (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2020)
This research was conducted to find out how the influence of firm size (X1) and debt to assets ratio (X2) on earnings per share in property and real estate companies listed on the Indonesia Stock Exchange, either partially or simultaneously. In addition, this research also investigates whether the return on equity (Z) variable was able to moderate the effect of firm size (X1) and debt to assets ratio (X2) simultaneously on earnings per share of property and real estate companies. The research data used was data from property and real estate companies during 2014-2018 and is taken from idx.co.id. The population in this research amounted to 55 property and real estate companies with 41 companies as the sample. This research was conducted in 2020. This research used quantitative data that was processed with SPSS 24.0 with moderated regression analysis (MRA). The results showed that firm size had no significant effect on earnings per share, while the debt to assets ratio had a positive and significant effect on earnings per share. Simultaneously, firm size and debt to assets ratio had a positive and significant effect on earnings per share. Return on equity was able to moderate with a significant effect of firm size and debt to assets ratio on earnings per share. The contribution before moderation was 12.8% while the contribution after moderation was 79.0%. Firm size and debt to assets ratio was not closely related to earnings per share.